Proceedings of the conference libration point orbits and applications, Aiguablava, Spain, 10 - 14 June 2002 (World Scientific, 2003)
This book presents the state of the art in numerical and analytical techniques as well as future trends associated with mission design for libration point orbits. It contains papers explaining theoretical developments and their applications, including the accurate description of some actual libration point missions of ESA and NASA. The existing software in the field and some applications beyond the neighborhood of the Earth are also presented. Special emphasis is placed on the use of dynamical systems methodology in the libration-point-orbits mission design.